Extracellular Signal-Regulated Kinase Is a Direct Target of the Anti-Inflammatory Compound Amentoflavone Derived from Torreya nucifera - Jueun Oh; Ho Sik Rho; Yanyan Yang; Ju Young Yoon; Jongsung Lee; Yong Deog Hong; Hyeon Chung Kim; Sun Shim Choi; Tae Woong Kim; Song Seok Shin; Jae Youl Cho (Hindawi Limited, 2013)
Amentoflavone is a biflavonoid compound with antioxidant, anticancer, antibacterial, antiviral, anti-inflammatory, and UV-blocking activities that can be isolated from Torreya nucifera, Biophytum sensitivum, and Selaginella tamariscina. In this study, the molecular mechanism underlying amentoflavone's anti-inflammatory activity was investigated. Amentoflavone dose dependently suppressed the production of nitric oxide (NO) and prostaglandin E2 (PGE2) in RAW264.7 cells stimulated with the TLR4 ligand lipopolysaccharide (LPS; derived from Gram-negative bacteria). Amentoflavone suppressed the nuclear translocation of c-Fos, a subunit of activator protein (AP)-1, at 60 min after LPS stimulation and inhibited the activity of purified and immunoprecipitated extracellular signal-regulated kinase (ERK), which mediates c-Fos translocation. In agreement with these results, amentoflavone also suppressed the formation of a molecular complex including ERK and c-Fos. Therefore, our data strongly suggest that amentoflavone's immunopharmacological activities are due to its direct effect on ERK.